Anemia Hemolitik Disebabkan Infeksi Kongenital Citomegalovirus - Indah Afriwanty Simatupang; Ricke Loesnihari; Wan Tysa Muhaira (Pusat riset dan Inovasi Nasional, 2025)
Hemolitic anemia is a condition of anemia caused a shortened lifespan of eritrocytes due to an increase in a rate of eritrocytes destruction higer than eritrocytes production in the bone marrow. Congenital Citomegalovirus Infection (CMV) is one of the most common viral infections that causes congenital infections. CMV is transmitted by contact with an individual who carries CMV infection. Approximatelly 90% of congenitally infected infants develop symptoms at birth. Jaundice, petechiae, and hepatosplenomegaly are the three most common sequences in infants. Congenital CMV infection can be diagnosed by isolating the virus by urine and saliva within first three weeks of life. Case Description A 24-day-old baby comes with jaundice all the body since the age of 14 days. Innitially Indah Afriwanty Simatupang, Ricke Loesnihari. Congenital Citomegalovirus Infection., light carried out at hospital but there was no change, the the patient was referred to Adam Malik Hospital. From the examination it was found thrombocytopenia, metabolic acidosis, increased SGOT and SGPT, increased total bilirubin and direct bilirubin, decreased procalcitonin, positive anti CMV IgG, and positive IgG CMV (Avidity). CONCLUSION Based on the history of physical and laboratory examination, its supports the diagnosis of Congenital Cytomegalovirus Infectios.